Evaluation of the effect of bracket and archwire composition on frictional forces in the buccal segments - Sajan V Nair; Ratna Padmanabhan; P Janardhanam (Wolters Kluwer Medknow Publications, 2012)
Aim of the study: The aim of this study was to consider friction in buccal segment attachments during overjet reduction by means of sliding mechanics. Friction was compared in Stainless Steel, Titanium and Cobalt Chromium brackets, using Stainless Steel and Beta Titanium wires. Materials and Methods: This in-vitro study comprised 18 samples (6 x 3 brackets of different materials-stainless steel, titanium and cobalt chromium). Each jig comprised of a buccal segment model of two premolar brackets and a molar tube simulating the upper posterior buccal segment. Each jig was coupled with the wire of 0.019 x 0.025 inch dimension and was tested with a Universal Testing Machine. Ligation was achieved using low friction elastomeric modules (Slide TM , Leone, Italy), a non-conventional elastomeric module. Results: All three bracket systems showed significantly higher frictional forces for the beta titanium wire than for the stainless steel wire. When coupled with the stainless steel wire, the titanium bracket showed the least friction, followed by stainless steel and cobalt chromium brackets. When coupled with the beta titanium wire, the titanium brackets again showed the least friction; while the difference in frictional levels between the stainless steel and cobalt chromium brackets was not statistically significant. The titanium brackets showed the least friction among all the groups tested for both wires. Conclusion: Titanium bracket with Beta Titanium wires could and probably should be the alternative metal bracket used in the nickel sensitive patient.